2020
DOI: 10.1088/1757-899x/848/1/012089
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of paths and energy losses of high-energy ions in single-layered and multilayered materials

Abstract: Modern electronic systems and equipment used in aerospace and nuclear technology, as well as many scientific and medical devices, are used under the influence of a wide range of ionizing radiation (electrons, protons, heavy charged particles etc.). Protons or heavy charged particles exposure can lead to failures in the operation of spacecrafts electronic devices, which is associated with the radiation effects occurrence in an integrated circuits. One of the most effective ways to solve this problem is protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 10 publications
0
21
0
1
Order By: Relevance
“…So, the presence of Ni and NiO crystallites in the nanowires indicates the ferromagnetic and antiferromagnetic domains coexistence. 65 It is also noteworthy that the magnetic parameters of the samples for two different temperature ranges (4.2 and 300 K) are almost the same (Fig. 6 and 7).…”
Section: Magnetic Properties Studymentioning
confidence: 59%
“…So, the presence of Ni and NiO crystallites in the nanowires indicates the ferromagnetic and antiferromagnetic domains coexistence. 65 It is also noteworthy that the magnetic parameters of the samples for two different temperature ranges (4.2 and 300 K) are almost the same (Fig. 6 and 7).…”
Section: Magnetic Properties Studymentioning
confidence: 59%
“…The structural damages of the host-guest system modify the local free volume characteristics and, in consequence, the amplitude of various non-linear effects. The interaction of the ions with the system can be modeled using the dedicated software GEANT4 [ 231 , 232 , 233 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ott [7] noted that appropriate shielding materials for gamma and x-radiations must have a high magnetic permeability for them to take up the radiation fields adequately. Tishkevich et al, [8] showed that materials with huge atomic charge values have higher shielding efficiency against high-energy ions from the locus of direct ranges of particles.…”
Section: Introductionmentioning
confidence: 99%